Evaluating Education Payoff in Russia - Irina Denisova; Marina Kartseva (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
Degrees in Technology, Law or Economics are Better Rewarded by the Market. Based on: Beyond Transition. July - September 2006. № 11. С. 5. http://www.worldbank.org/transitionnewsletter